MEMBONGKAR EPISTEMOLOGI PENDIDIKAN KI HADJAR DEWANTARA DALAM KONTEKS POSTMODERNISME - Rizki Ramadan (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2025)
This study deconstructs the educational epistemology of Ki Hadjar Dewantara (KHD) through the lens of postmodern critique. Using a deconstructive approach, the research investigates the relevance and reinterpretation of KHD’s concepts of the "Tri-Center of Education" (family, school, society) and the among system within the context of postmodern epistemological relativism. The primary texts of KHD are analyzed alongside the theoretical frameworks of postmodern thinkers such as Jean-François Lyotard, Michel Foucault, and Jacques Derrida. The findings reveal both intersections and tensions between KHD’s humanistic vision of education and the postmodern skepticism toward grand educational narratives. On one hand, KHD’s educational philosophy resonates with postmodernism in its resistance to knowledge homogenization and singular authority. On the other hand, a critical gap exists between KHD’s ethical-spiritual orientation and the radical relativism of postmodernism, which often leans toward nihilism. Therefore, this study emphasizes the need to critically reconceptualize KHD’s educational values to remain relevant and transformative amid the fluid, plural, and uncertain conditions of contemporary education. This research contributes to the enrichment of locally grounded critical pedagogy that is culturally rooted yet responsive to global epistemic shifts.